Modeling Students' Perceptions of Chatbots in Learning: Integrating Technology Acceptance with the Value-Based Adoption Model - Ahlam Mohammed Al-Abdullatif (MDPI AG, 2023)
As technology continues to advance, chatbots are likely to become an increasingly vital tool in education. This study digs further into how students perceive and accept chatbots for use in learning activities. The study examines the integrated relationships between the constructs of the technology acceptance model (TAM) and the constructs of the value-based model (VAM), including perceived enjoyment, perceived risk, and perceived value, to predict students' attitudes and, consequently, their acceptance of chatbots for learning in higher education. A total of 432 respondents participated in an online survey, and the proposed hypotheses were evaluated through structural equation modeling (SEM-PLS). The study offers useful insights on chatbot adoption in Saudi higher education, as the results highlight important drivers of chatbot acceptance among students, including perceived usefulness, perceived ease of use, attitude, perceived enjoyment, and perceived value. Perceived risk was not a significant predictor of students' attitudes or their acceptance of chatbot use in learning. The results are expected to foster the adoption of chatbot technology in supporting distance learning in Saudi Arabia's higher education.